Ensino lúdico: o uso de brinquedo no ensino de ondulatória - COSTA, Cleiciane Balieiro da Silva da (Instituto Federal do Amapá, 2021)
One of the biggest challenges of teaching Physics is to overcome the barrier of traditional teaching. Therefore, it is necessary to search for new methodologies to work with this disciplines concepts in the classroom. A teaching method that has gained much space as pedagogical support, and is considered a fundamental tool for the student's teaching-learning process, is ludic activities. Thus, the present study aimed to analyze how toys can contribute to significant learning of sound waves in high school. It is applied research with a qualitative approach and descriptive purposes. Due to the Covid19 pandemic, the research was applied remotely to 3rd-grade class from high school in Santana-AP. A pre-test questionnaire was used to assess the students' previous knowledge about sound waves to achieve the determined objectives and carry out the data collection. After applying this questionnaire, the analysis of these data was carried out, and it was found that the students did not have sufficient knowledge about the content of sound waves. Then a video was made, produced by the own academics, containing the main concepts involving the content and associating them with toys. Finally, to carry out the impact assessment, a post-test questionnaire was applied to verify how the learning took place and compare the data since it hears students' learning regarding the content worked on in this research. Therefore, it is concluded that the teaching of sound waves becomes significant with the use of toys.